Effects and Implications of COVID-19 for the Human Senses, Consumer Preferences, Appetite and Eating Behaviour - Byrne, Derek V. (2022)
As Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) evolved into a global pandemic, assessments of coronavirus disease 19 (COVID-19) patients have presented health conditions including, in many cases, a mild to severe loss of smell and tasting abilities among patients. Initial work has shown short and likely longer term negative effects on the human senses, with some indications of effects on consumer preferences; however, as of yet, very little is known about the impacts on eating behaviours and consequent longer term effects on appetite. The aim of this Special Issue anthology was, for the first time, to bring together researchers with key insights into how COVID-19 has impacted appetite and eating behaviours from the fundamental to the applicable, as assessed by human sensory perception. Thus, research is included that explores various themes, from the basic effects on the senses, to changes in consumer preferences, all the way to how and why COVID-19 has changed consumer behaviours in relation to food and eating in the longer term. Overall, we wished to document and bring together key research in the sensory and consumer space with respect to COVID-19, with the overall aim to highlight and ensure this research has a lasting impact regarding future understandings of measures developed to help and treat people affected during the ongoing pandemic.